Identification and Strain Differentiation of Vibrio cholerae by Using Polyclonal Antibodies against Outer Membrane Proteins - Martínez-Govea, A. (American Society for Microbiology, 2001)
Cholera is caused only by O1 and O139 Vibrio cholerae strains. For diagnosis, 3 working days are needed for bacterial isolation from human feces and for biochemical characterization. Here we describe the purification of bacterial outer membrane proteins (OMP) from V. cholerae O1 Ogawa, O1 Inaba, and O139 strains, as well as the production of specific antisera and their use for fecal Vibrio antigen detection. Anti-OMP antisera showed very high reactivity and specificity by enzyme-linked immunosorbent assay (ELISA) and dot-ELISA. An inmunodiagnostic assay for V. cholerae detection was developed; this assay avoids preenrichment and costly equipment and can be used for epidemiological surveillance and clinical diagnosis of cases, considering that prompt and specific identification of bacteria is mandatory in cholera.